A Hypothetical Reconstruction of the Lost Qurʼānic Commentary of Jalāl al-Dīn al-Suyūṭī (d. 911/1505) (Part 1) - Azam Bahtiar; Muammar Zayn Qadafy (Al-Jami'ah Research Centre, 2025)
This article constitutes the first section of a two-part study designed to form a single, coherent work on a hypothetical reconstruction of the lost Qurʼānic commentary of al-Suyūṭī, Majmaʻ al-Baḥrayn wa Maṭlaʻ al-Badrayn. The present part serves as an introduction, offering a critical investigation into the scholarly persona of the Egyptian polymath of the Burjī Mamlūk period. It focuses particularly on the complexity of his intellectual persona as a prolific author, followed by an examination of how he conceived of himself as a Qur’anic exegete and how transmitted reports (riwāyāt) occupied a position of high authority within his exegetical framework. Al-Suyūṭī engaged in intense scholarly confrontations with his contemporaries, most notably al-Sakhāwī (d. 902/1497), which involved accusations of plagiarism and sharp criticism of his intellectual methods. Conversely, his defense of Sufi figures such as Ibn ʻArabī (d. 638/1240) against charges of takfīr reveals a pronounced spiritual inclination, an aspect often overshadowed by his image as a muḥaddith–cum–exegete employing a radical report-based method in al-Durr al-Manthūr. Within the broader field of Qurʼānic exegesis, al-Suyūṭī is generally recognized through five works: al-Itqān, al-Durr al-Manthūr, Qaṭf al-Azhār, Nawāhid al-Abkār, and the first part of Tafsīr al-Jalālayn. We argue that only when these five works are considered collectively can one begin to apprehend the ambitious and comprehensive exegetical project that reflects al-Suyūṭī’s original scholarly vision.[Artikel ini merupakan bagian pertama dari sebuah kajian dua bagian yang dirancang untuk membentuk satu karya utuh dan koheren mengenai rekonstruksi hipotetis atas tafsir al-Qur’an karya al-Suyūṭī yang telah hilang, Majmaʻ al-Baḥrayn wa Maṭlaʻ al-Badrayn. Bagian ini berfungsi sebagai pendahuluan dengan menyajikan telaah kritis terhadap sosok intelektual polymath Mesir pada periode Mamlūk Burjī tersebut. Kajian ini secara khusus menyoroti kompleksitas persona intelektualnya sebagai seorang penulis yang sangat produktif, diikuti dengan pembahasan mengenai bagaimana ia memandang dirinya sebagai seorang mufasir al-Qur’an serta bagaimana riwayat-riwayat transmisi (riwāyāt) menempati posisi otoritatif dalam kerangka penafsirannya. Al-Suyūṭī terlibat dalam berbagai konfrontasi ilmiah yang intens dengan para cendekiawan sezamannya, terutama dengan al-Sakhāwī (w. 902/1497), yang mencakup tuduhan plagiarisme serta kritik tajam terhadap metode intelektualnya. Di sisi lain, pembelaannya terhadap tokoh-tokoh sufi seperti Ibn ʻArabī (w. 638/1240) dari tuduhan takfīr menunjukkan kecenderungan spiritual yang kuat, suatu aspek yang kerap terabaikan oleh citranya sebagai seorang muḥaddith sekaligus mufasir yang menerapkan metode penafsiran berbasis riwayat secara radikal dalam al-Durr al-Manthūr. Dalam ranah tafsir al-Qur’an yang lebih luas, al-Suyūṭī umumnya dikenal melalui lima karya utama: al-Itqān, al-Durr al-Manthūr, Qaṭf al-Azhār, Nawāhid al-Abkār, dan bagian pertama dari Tafsīr al-Jalālayn. Kami berargumen bahwa hanya dengan mempertimbangkan kelima karya tersebut secara kolektif, seseorang dapat mulai memahami proyek tafsir yang ambisius dan komprehensif, yang mencerminkan visi intelektual orisinal al-Suyūṭī.]